Instalasi Sistem Filtrasi Elektrokoagulasi Sebagai Penjernian Air Keruh Pada Kolam Renang Wisata Padusan Di Mojokerto - Dani Irawan; Erwin Komara Mindarta; Retno Wulandari; Monika Dwi Laily; Andri Wisnu Wardana (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Swimming pools as public facilities that are crowded with people can potentially become a means of spreading germs and health problems due to poor environmental sanitation conditions and polluted pool water quality. Polluted swimming pool water quality can also be a means of spreading disease germs and health problems. Based on this background, the community service team through UM's internal funds intends to conduct community service as part of the tri dharma of higher education with the aim of (1) Creating and implementing a filtration system in the Padusan Tourism swimming pool that can be controlled remotely based on the Internet of Thinks ( IOT) with the type of filtration, (2) Conduct installation technical guidance on the Electrocosgulation Filtration System so that the results of water purification and pool cleanliness can be maintained properly. The method used in this community service activity is community empowerment through training and mentoring. The implementation of community service through counseling on swimming pool filtration equipment has had a positive impact and can increase understanding for residents who have swimming pool management. This can be seen from the interest and agreement between the village head and residents to produce the waste filter equipment themselves. As well as changes in the behavior of housewives in terms of limiting the use of water from springs and river water for bathing, irrigation, and consumption by livestock. In addition, this counseling activity showed that there was an increase in the understanding of Padusan Village residents as participants in this activity which was indicated by the correct answers in the question and answer process by the presenters.